SISTEM INFORMASI ABSENSI SISWA (STUDI KASUS PERGURUAN ISLAM MATHALI’UL FALAH PATI JAWA TENGAH) - Atin Triwahyuni (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2012)
Mathali'ul Falah Pati Islamic Education in Central Java is the institution of education elementary school level (Islamic elementary schools) to high school (Madrasah Aliyah). In the daily operations of a lot of conventional process is done, one of which is the administration of absentee / attendance. The main difficulty encountered is in the data summary attendance / attendance either daily, weekly or monthly due to having to browse the files one by one absentee. The purpose of this research is to develop an information system attendance using a structured system development model. With the help of a specialized information system to facilitate the attendance data processing administrative data processing and report absences. From the research conducted it can be seen that attendance information system can accommodate the needs of users in managing attendance and presenting summary reports periodically.